"If You’re Going Through Something Difficult, We’d Like To Help": The Limitations Of Hashtag Logics In Pro-Eating Disorder Content Moderation - Gerrard, Ysabel (AoIR Selected Papers of Internet Research, 2017)
This paper addresses the ways that Instagram and Tumblr’s algorithmic cultures are shaped by public discourses about eating disorders (ED). It offers one of the few scholarly responses to recently re-ignited debates about media technologies’ supposed responsibility for a rise in cases of eating disorders, particularly amongst girls and young women (see also Chancellor et al, 2016). It analyzes the platforms’ methods of algorithmic control, such as banning certain pro-ED terms (e.g., #proana, #thinspiration and #thighgap) and prompting messages to users before they can view certain hashtags (e.g., #anorexia). It also examines the types of ED hashtags and visual images that users share, such as untagged images, creating space for users to share what might be equally troubling images as well as work around hashtags. Put simply, it seeks to understand how algorithms are _entangled_ with users’ practice (see Gillespie, 2014). Using a combination of traditional and digital research methods, the project considers how Instagram and Tumblr's hashtag bans and other technical responses have led to the formation of new hashtag publics (see Rambukkana, 2015; Bruns et al, 2016). It addresses the extent to which hashtag cultures are platform-specific, as users’ negotiations are shaped by the platforms' norms and technical affordances. Although Chancellor et al (2016) have considered the link between ED and social media's algorithms, they have not yet considered their gender politics. As public discourses about ED are typically feminized (see Holmes, 2016), the paper takes a feminist approach to examine this socio-technical issue.